A process model for designing performance dashboard using visualization techniques / Muhammad Nasim Bahar - Muhammad Nasim , Bahar (2020)
Data visualization is the presentation of data in a pictorial or graphical format. It enables decision-makers to see data analysis presented visually, so they can observe difficult concepts or identify new patterns. With interactive visualization, we can take the concept a step further by using technology to drill down into charts and graphs for more detail, interactively changing what data see and how it is processed. With the help of data visualization, it is expected to promote creative data exploration. A performance dashboard is one of the most common use cases for data visualization, and it enables decision-makers such as executives and managers to monitor the performance of an organization at one glance. It is essential to go through a proven process model that includes all aspects of designing a performance dashboard. To date, there is a lack of systematic process to design a performance dashboard that using the right performance metrics to measure the Key Performance Indicators (KPIs) and selecting appropriate visualization techniques for visualizing the performance analysis in a dashboard. This research aim is to propose a new process model for designing a performance dashboard using the visualization technique. A case study was conducted to evaluate the functional suitability and usability of the proposed process model by developing a taxation performance dashboard. The evaluation results show that it is feasible to apply the proposed process model to design am effective and usable performance dashboard for analyzing and monitoring the performance of a department.